The Role of HIF-1alpha in Regional Lymph Nodes Metastasis in Colorectal Adenocarcinoma - Rumapar, Ladyna; Mustokoweni, Sjahjenny; Rahniayu, Alphania (Folia Medica Indonesiana, 2018)
Colorectal carcinoma has high morbidity and mortality rate worldwide, in which over 90% are adenocarcinoma. Colorectal carcinoma is one of the most cancer that metastasize to the lymph node. Angiogenesis have an important role in tumor growth and metastasis. Hypoxia is the trigger factor for angiogenesis. Hypoxia induced factor-1 (HIF-1) is one critical protein directly reacting to hypoxia. HIF-1alpha, a HIF-1 subunit, is an important regulator of angiogenesis. This study analyzed HIF-1a expression in colorectal adenocarcinoma with and without regional lymph node metastasis. This study was to prove that HIF-1a has a role in regional lymph node metastasis in colorectal adenocarcinoma. An analytical observational study was conducted on thirty formalin fixed paraffin-embedded colorectal adenocarcinoma tissues from Anatomic Pathology Laboratory of Dr. Soetomo Hospital. Detection of HIF-1alpha expressions were performed with immunohistochemistry method, using HIF-1alpha antibody. It were statistically analyzed using Mann-Whitney and Kruskal- Wallis methods. There were no significant differences in the expression of HIF-1alpha in colorectal adenocarcinoma with or without lymph node (LN) metastasis (p>0.05). As a conclusion, this study showed that HIF-1alpha has no role in LN metastasis in colorectal adenocarcinoma.